PERAN PROGRAM PENGENALAN LINGKUNGAN PERSEKOLAHAN (PLP) II DALAM MEMBENTUK PROFESIONALISME MAHASISWA CALON GURU - Nurfahmariani; Nursyam, Hilda; Latifah, Wulan; Pausia Paharani, Ita; Rahmadani Haswan, Ela; Anggriani Shaleh, Nur; Selviana; Wahyuni, Sri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The School Environment Orientation Program (PLP) II is an academic program designed to provide education students with hands-on experience in understanding the school environment and teaching practices. This program plays a crucial role in fostering the professionalism of students as future educators. This study aims to describe the implementation of PLP II and analyze its role in developing students’ professional competencies in schools. The study employs a qualitative descriptive method, utilizing data collection techniques such as observation, documentation, teaching practice, and students’ direct experiences during the implementation of PLP II. Data were analyzed through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the implementation of PLP II provides students with real-world experience in understanding school administration, the learning process, classroom management, communication with students, and collaboration with educators at the school. Additionally, this program enhances students’ pedagogical, social, professional, and personal competencies as prospective teachers. Students also experienced an increase in their sense of responsibility, discipline, communication skills, and self-confidence in conducting learning activities. Thus, PLP II plays a strategic role in preparing education students to be better prepared to face the professional world as educators.